Psychological Factors Associated With Students' Academic Achievement in An International School in Kuala Lumpur. - Uguak, Uget Apayo (2005)
This study investigated the relationship between psychological factors and students' academic achievement among foreign students in an international school in Kuala Lumpur. The academic achievement of the students in the target international school was unevenly distributed among the students. This uneven distribution was studied to identify the psychological factors that best predicted the students' academic achievement. The research employed an ex post facto design and the data was collected through a set of questionnaires. One hundred and fifty subjects were randomly selected out of seven classes based on Kerlinger and Pedhazur (1973); Cohen's (1988) principles and formula respectively Both descriptive and inferential statistics were used to analyze the data in the study using SPSS. The statistical techniques used were Descriptive Statistics, Independent-Sample t-test, Analysis of Variance (ANOVA), Pearson Product Moment Correlation (r), and Multiple Linear Regression. The research findings showed that there was no statistical sigruficant difference between female and male students on psychological factors (adjustment, motivation, attitude, locus of control, self-efficacy, and attribution). The findings also revealed that the primary and secondary levels were significantly different only on locus of control. A positive and significant relationship was also found between psychological factors and academic achievement with strengths ranging between moderate and low. The results of the multiple regression analysis showed that attribution, adjustment, self-efficacy, and attitude were signhcant predictors of academic achievement. The R2 .547 implies that the four predictor variables explain about 54.7% of the variance in academic achievement. On the other hand, Locus of control and motivation were not significant but positively related to academic achievement. Generally, the findings indicated that the four psychological factors were the most significant factors in explaining the variance of academic achievement.